The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.3390/ijerph13080778
|View full text |Cite
|
Sign up to set email alerts
|

High Laccase Expression by Trametes versicolor in a Simulated Textile Effluent with Different Carbon Sources and PHs

Abstract: Textile effluents are highly polluting and have variable and complex compositions. They can be extremely complex, with high salt concentrations and alkaline pHs. A fixed-bed bioreactor was used in the present study to simulate a textile effluent treatment, where the white-rot fungus, Trametes versicolor, efficiently decolourised the azo dye Reactive Black 5 over 28 days. This occurred under high alkaline conditions, which is unusual, but advantageous, for successful decolourisation processes. Active dye decolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 46 publications
2
3
0
Order By: Relevance
“…Among the tested substances, glycerol and Tween 80 were the best Lac inducers. A similar increase in Lac production in response to the addition of glycerol has been reported about different whiterot fungi [22,53]. Furthermore, Tween 80 and veratryl alcohol significantly improve MnP production by T. trogii in every concentration used in the study.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Among the tested substances, glycerol and Tween 80 were the best Lac inducers. A similar increase in Lac production in response to the addition of glycerol has been reported about different whiterot fungi [22,53]. Furthermore, Tween 80 and veratryl alcohol significantly improve MnP production by T. trogii in every concentration used in the study.…”
Section: Discussionsupporting
confidence: 85%
“…Different natural or synthetic agents have been used to induce the synthesis of ligninases [11,13,15,43]. A similar increase in Lac production in response to the addition of glycerol has been reported about different whiterot fungi [22,53]. Among the tested substances, glycerol and Tween 80 were the best Lac inducers.…”
Section: Discussionsupporting
confidence: 55%
“…The use of oxidative enzymes, mainly Lac and peroxidases, in textile industry has increased quickly. It has been due to both: (a) the ability of these oxidative enzymes to bleach textiles; and (b) the biological treatments involving these enzymes seem to be an attractive solution mainly because most existing treatments (e.g., coagulation/flocculation, adsorption, ion exchange, and electrochemical methods) of dye wastewater utilize ineffective and uneconomical processes [ 12 ]. In addition, other biomimetic oxidative bleaches, like metalloporphyrins, are very promising catalysts for synthetic textile dyes.…”
Section: Introductionmentioning
confidence: 99%
“…These laccase isoforms can be assumed to be partially responsible for the increased oxidative potential observed for both OPE and veratryl alcohol (Figure 2B). Ottini et al also reported the upregulation of a laccase-encoding gene homologous to LCC3 in T. versicolor MUM 04.100 when cultivated in the presence of alternative carbon sources [51]. The shaken submerged cultures of T. M99 were prepared with 20% OPE or 5 mM veratryl alcohol, added from the start of the experiment.…”
Section: Effects Of Orange Peel Extract and Veratryl Alcohol On The T...mentioning
confidence: 99%